The Language Features Used by Jehian Panangian when Having Conversations with Raymond Chin and Hermanto Tanoko in Podcasts - Valentina Chrysanti Herjanto; Henny Putri Saking Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study identifies the language features used by Jehian Panangian in same-sex conversations with different addressees, Raymond Chin (same age and status) and Hermanto Tanoko (older and higher status), in podcasts. It also explores the differences and similarities in Jehian’s utterances when conversing with each addressee, utilizing Coates’ (2013) language features theory and Holmes’ (2013) theories on age and status. Jehian's utterances were transcribed and analyzed using a qualitative approach. The findings showed that Jehian used swearing and taboo language and compliments with Raymond but not with Hermanto. Jehian used more minimal responses, tag questions, and commands and directives with Raymond. Jehian also used more casual expressions and different functions on particular language features. Despite these differences, the dominant and less frequently used language features were similar in both conversations. In conclusion, the addressee’s age and status significantly influenced the speaker’s language features, alongside the host’s style and discussion topic.